Holistic Management of Hypertension and Hypercholesterolemia Patients with Vertigo Through a Family Medicine Approach: Penatalaksanaan Holistik Pasien Hipertensi dan Hiperkolesterolemia dengan Vertigo Melalui Pendekatan Kedokteran Keluarga - Hero, Syifa Khairunnisa; Nusadewianti, Azelia (CV. Jasa Sukses Abadi, 2024)
Hypertension is one of the most common problems that occurs in the population, whether diagnosed or not. Cholesterol levels are closely related to hypertension and its complications. The characteristic of geriatric patients is multipathology. In hypertensive patients with hypercholesterolemia, it is very likely to cause vertigo. Vertigo or in Latin, Vertere, means twisting. In general, vertigo is known as a syndrome that occurs due to disturbances in the balance system. Implement family doctor services based on evidence-based medicine holistically and comprehensively for patients by identifying risk factors, clinical problems, and patient management based on a framework for solving patient problems using a patient-centered, family approach, and community-oriented approach. The study carried out a case report by carrying out an overall assessment, namely history taking, physical examination, and visits to the patient's home to assess the environment. Secondary data was obtained from the patient's medical records. Assessment is based on a holistic diagnosis of the beginning, process, and end of the study qualitatively and quantitatively. Based on an examination of a 70-year-old male patient with complaints of dizziness, nausea, vomiting, and blurred to dark vision. The patient also admitted that he had soreness in his neck and shoulders. The patient admitted that the complaints came and went. On physical examination, it was found to be within normal limits. On supporting examinations, high cholesterol levels were found. Holistic and comprehensive management was carried out. Services with a family medicine approach in pharmacological and non-pharmacological therapy can solve health problems and improve the patient's quality of life. The role and support of the family is very much needed in monitoring.